Milk alkali syndrome in an infant with chronic kidney disease - Kari JA; El Desoky SM (Dove Medical Press, 2012)
Jameela A Kari, Sherif M El DesokyDepartment of Pediatrics and Pediatric Nephrology Unit, King Abdulaziz University, Jeddah, Kingdom of Saudi ArabiaAbstract: We report a case of milk alkali syndrome in a 15-month-old infant who had chronic kidney disease. His kidney function worsened, with creatinine raised from 1.11 mg/dL (98 µmol/L) to 3.98 mg/dL (350.3 µmol/L), normal 0.4–1.0 mg/dL (35–91 µmol). He had hypercalcemia, serum calcium level 3.11 (normal 2.1–2.6) mmol/L, and metabolic alkalosis, HCO3 48.7 (normal 21–26) mmol/L. His kidney function returned to its base level and his calcium and bicarbonate levels normalized with adjustment of calcium carbonate and sodium bicarbonate doses. We report this case to highlight an unusual complication and to review the literature on milk alkali syndrome which is rare in children.Keywords: milk alkali syndrome, infants, chronic kidney disease